On the Raetian-Alemannic Connections with Istria, Dalmatia and Carantania in the Carolingian Age – Two Examples - Štih, Peter (ASPICE HUNC OPUS MIRUM: zbornik povodom sedamdesetog rođendana Nikole Jakšića, 2020)
Frankish rule over the Lombard Kingdom rested largely upon people who arrived in Italy from the area to the north of the Alps. The distinguished noble families that established themselves in north-eastern Italy (Friuli, Istria) included also the Frankish(?) Unruochings and the Raetian-Alemannic Hunfridings. The article addresses their members’ lesser known contacts with Istria and the Slavic hinterland from Carantania to Dalmatia. Hunfrid I and his son Hunfrid II were counts in Raetia and were active in Italy as missi of Charlemagne and Louis the Pious, during whose lifetimes they administered Istria, which became an important centre of the Hunfridings’ power. Albgar, on the other hand, who travelled to Dalmatia as a missus of Louis the Pious in 817 to settle the disputes between the Slavs and the Romans, was a member of the Unruochings. He was a cousin of Eberhard, Duke of Friuli, who was married to Gisela, daughter of Louis the Pious. He came to Italy as a tutor, baiolus, of King Pippin’s daughter, and left it after the king’s death for a long time. He was attested as Count of Alemannia around 830, whereupon he was very probably Count of Carantania until his return to northern Italy around 840, where he spent his old age living near Lago Maggiore. The contacts and connections of the Frankish elite with their Slavic peers on the empire’s south-eastern border were much more intensive than they appear to be at first glance. They are well-documented, inter alia, by libri vitae from Salzburg and Cividale, where Frankish and Slavic magnates from a large contact area, extending from Moravia and Pannonia to Carantania and Dalmatia, are often entered alongside each other.